Pengaruh Pesan Tagline Baru "Tropical Adventure" Terhadap Kepercayaan Merek Eiger (Survei Pada Ukm Mapala Universitas Di Jakarta) - Farhan Zikri Zaidan Karim, (2020)
This study discusses the effect of the new tagline "Tropical Adventure" on the Eiger Brand Trust. The purpose of this study is to determine whether there is an influence of the new tagline "Tropical Adventure" on the trust of the Eiger brand, and to find out how much influence. The theory used in this research is the S-O-R (Stimulus-Organism-Response) Theory. The method used is a quantitative research method. Data collection is done by distributing questionnaires. The population in this study were members of the University of Jakarta nature lover student activity unit, for samples using the Lemeshow formula which were then obtained as many as 96 respondents. The sampling technique used in this study is the cluster sampling technique. Data processing in this study uses SPSS version 25 for Windows. Based on the calculation of the coefficient of determination obtained the effect of tagline on brand trust by 32.9%, while the remaining 67.1% is the influence of other variables not examined in this study. The results of testing the hypothesis using the t test showed that t count 6.784 > t table 1.665, it can be concluded that H0 was rejected and Ha was accepted. R value obtained through the correlation test of 0.573 which is in the category of interpretation of the correlation coefficient shows a fairly strong level of influence. So, it can be known and concluded that the new tagline "Tropical Adventure" has a strong enough influence on the trust of the Eiger brand on members of the University's nature lover student activity unit in Jakarta.